Active network management scheme for reactive power control - Sirviö, Katja; Laaksonen, Hannu; Kauhaniemi, Kimmo (CIRED, 2018)
In the future new options to provide needed technical ancillary services locally and system-wide by distributed energy resources (DER) are needed. One ancillary service which DER could provide is the reactive power management when microgrid is operated in utility grid-connected mode. In this paper different requirements for reactive power flow between distribution and transmission grids were considered in Sundom Smart Grid (SSG) and the measured data from SSG was used for developing a concept for reactive power management. Based on these different requirements “Future Reactive Power Window” was formulated for SSG which was the basis for control scheme formulation. The simulations showed that coordinated reactive power management scheme across different voltage levels by utilizing control of distributed generation could be very beneficial to the voltage support ancillary service.
Keywords: electrical power networks; distribution of electricity; reactive power; renewable energy sources; parallel publishing; transmission of electricity; energy systems; Finland; power electronics; electric power; fi=Sähkötekniikka|en=Electrical Engineering|